Mental Health of Hmong Americans: A Metasynthesis of Academic Journal Article Findings - Song E. Lee (Hmong Studies Journal, 2013)
The mental health of Hmong Americans has been studied since their arrival in the United States. The purpose of this metasynthesis is to utilize a qualitative approach to analyze academic journal article studies that assess mental health issues in Hmong Americans. Forty-eight published articles from 1983 to 2012 were chosen for analysis. Each of the selected articles focused on Hmong participants and contained findings relevant to the psychological well-being of Hmong Americans. Results of this study revealed several common themes: trends in research, depression, anxiety, adjustment issues, family issues, substance abuse, other mental health concerns, factors linked to mental health, help seeking behavior and perceptions, effectiveness of mental health treatments, strengths and resiliency, and supportive factors.